Qur’anic Intertextuality in Mohtasham Kashani’s Davazdah-Band: A Genettian Perspective - Salsabila, Regina; Sakinah, R. Myrna Nur (Lembaga Publikasi Ilmiah Dwipantara, 2025)
Religious poetry in the Shi’a tradition serves not only as a medium of mourning but also as a vehicle for theological expression and spiritual reflection. Mohtasham Kashani’s Davazdah-Band, a central elegy in classical Persian literature, intricately weaves Qur’anic references into its portrayal of the Karbala tragedy. Despite its cultural significance, the poem has received limited scholarly attention in terms of its intertextual engagement with the Qur’an, particularly in Indonesian academic discourse. This study investigates how Qur’anic verses are embedded, recontextualized, and transformed within Davazdah-Band to reinforce Shi’a theological ideals. Employing a qualitative-descriptive approach based on Gérard Genette’s theory of transtextuality, the research identifies instances of direct quotation, thematic allusion, and symbolic transformation. The analysis reveals that Qur’anic imagery, such as water, blood, patience, and sacrifice, is repurposed to sacralize the suffering of Husayn and legitimize the Shi’a worldview. The elegy thus becomes a site of devotional performance, where poetic form and sacred text converge to construct collective memory and religious identity.